Privatization of Military Activities: Private Military and Security Companies and Their Impact on International Humanitarian Law - Ayad Hilal Hussein Al-Kanani (International Journal of Law Research and Studies, 2025)
In recent decades, the international system has witnessed a profound transformation in the structure of actors, whereby the nation-state no longer exclusively holds the means of force or the functions of security and defense. Instead, private entities—particularly Private Military and Security Companies (PMSCs)—have increasingly taken on roles traditionally reserved for regular armed forces, including combat operations, military training, logistical support, and the protection of vital facilities. This transformation presents significant legal challenges, especially concerning the legal nature of these companies, the status of their personnel under International Humanitarian Law (IHL), and the extent to which they are bound by its rules and principles. This study aims to analyze the legal status of PMSCs and their personnel, to determine whether they fall under the obligations of IHL, and to examine the possibility of subjecting them to international legal responsibility. It also explores the impact of their engagement in armed conflicts on core humanitarian principles—particularly the principles of distinction between combatants and civilians, proportionality in the use of force, and state responsibility for violations. Moreover, the study addresses the legal void resulting from the absence of direct international legal personality for these companies, which allows them to operate beyond effective oversight, particularly in fragile conflict environments. The study concludes that the privatization of military functions undermines the effectiveness of the international legal protection system, erodes the distinction between civilians and combatants, and weakens the principle of the state’s monopoly on the legitimate use of force. It also shows that responsibility does not lie solely with individual actors but extends to the states contracting these companies, which are legally obligated to ensure their compliance with IHL. The study ultimately calls for the development of a binding and coherent international legal framework to regulate PMSCs, establish effective accountability mechanisms, and reaffirm the foundational humanitarian principles of IHL.